2003
DOI: 10.1002/ijc.11597
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukemia and road traffic: A population‐based case‐control study

Abstract: To assess the effect of road traffic exhaust on the risk of childhood leukemia, we carried out a population-based casecontrol study in the Province of Varese, northern Italy, covered by a population-based cancer registry. All 120 incident cases from 1978 -97 were included in the study. Four controls per case, matched by age and gender, were sampled from population files. As index of exposure to traffic exhaust we estimated the annual mean concentration of benzene outside the home using a Gaussian diffusion mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 23 publications
7
87
0
2
Order By: Relevance
“…Our study in the context of previous studies 12 Our results are consistent with the findings of some but not all previous studies of childhood cancer and residence in the proximity to highly trafficked roads [9,[24][25][26][27][28]. The largest of these studies, based on over 700 cases of ALL, found a doubling of the risk among children living within 500 m of high-speed highways and main roads compared to unexposed children [9].…”
Section: Main Findingssupporting
confidence: 92%
“…Our study in the context of previous studies 12 Our results are consistent with the findings of some but not all previous studies of childhood cancer and residence in the proximity to highly trafficked roads [9,[24][25][26][27][28]. The largest of these studies, based on over 700 cases of ALL, found a doubling of the risk among children living within 500 m of high-speed highways and main roads compared to unexposed children [9].…”
Section: Main Findingssupporting
confidence: 92%
“…There has been growing interest in evaluating exposure to vehicle exhaust for epidemiologic studies of lung cancer (1,2), childhood cancer (3)(4)(5)(6), breast cancer (7), asthma (8)(9)(10), respiratory symptoms (11), all cause mortality (12), and birth outcomes (13)(14)(15)(16). These studies often rely on exposure estimates derived from surveys or a geographic information system (GIS).…”
Section: Introductionmentioning
confidence: 99%
“…One ecologic study in Sweden found a significant relationship between car density and childhood leukemia [25]. A population based case control study in northern Italy similarly found a significant relationship between traffic density (vehicles/ day) and childhood leukemia [34]. However, another study that looked at a population from a previous case control study in Los Angeles was not able to find any association between traffic density and childhood leukemia [35].…”
Section: Figmentioning
confidence: 99%
“…NHL is also more common in Caucasians than in African-Americans and more common in males than in females [4]. Based on epidemiologic findings, Hodgkin's Disease (HD) can be divided into three different diseases: childhood (0-14), young adult (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and older adult (> 55) HD [6]. A relationship between Epstein-Barr virus (EBV) infection and the risk of HD has been established, but the underlying mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%